4-(Succinimido)-1-butane Sulfonic Acid as a Brönsted Acid Catalyst for Synthesis of 4, 4′-(arylmethylene)bis(1H-pyrazol-5-ol)s Derivatives under Solvent-Free Conditions. (19th October 2016) - Khaligh, Nader Ghaffari; Titinchi, Salam J. J.; Hamid, Sharifah Bee Abd; Abbo, Hanna S.
Abstract : 4-(Succinimido)-1-butane sulfonic acid as a efficient and reusable Brönsted acid catalyzed the synthesis of 4, 4′-(arylmethylene)bis(1H-pyrazol-5-ol) derivatives under solvent-free conditions. The catalyst can be prepared by mixing succinimide and 1, 4-butanesultone that is simpler and safer than the preparation of succinimide sulfonic acid. This method has the advantages of high yield, clean reaction, simple methodology, and short reaction time. The catalyst could be recycled without significant loss of activity.